2013
DOI: 10.3390/v5112624
|View full text |Cite
|
Sign up to set email alerts
|

Role of Innate Immunity against Human Papillomavirus (HPV) Infections and Effect of Adjuvants in Promoting Specific Immune Response

Abstract: During the early stages of human papillomavirus (HPV) infections, the innate immune system creates a pro-inflammatory microenvironment by recruiting innate immune cells to eliminate the infected cells, initiating an effective acquired immune response. However, HPV exhibits a wide range of strategies for evading immune-surveillance, generating an anti-inflammatory microenvironment. The administration of new adjuvants, such as TLR (Toll-like receptors) agonists and alpha-galactosylceramide, has been demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
120
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(147 citation statements)
references
References 95 publications
4
120
0
6
Order By: Relevance
“…26 HPV infection, and in particular chronic persistent infection, involves viral modulation of the immune microenvironment within the lesion (wart). 27,28 This viral immune manipulation includes primarily a shift toward a Th2 response with an increase in cytokines such as IL-10, which is inefficient at clearing the infection. 28,29 It is logical to assume that, if acupuncture treatment can restore the balance of the Th1/Th2 response in Th2-related diseases as noted, it may be possible to do so in the case of chronic HPV infection.…”
Section: Introductionmentioning
confidence: 99%
“…26 HPV infection, and in particular chronic persistent infection, involves viral modulation of the immune microenvironment within the lesion (wart). 27,28 This viral immune manipulation includes primarily a shift toward a Th2 response with an increase in cytokines such as IL-10, which is inefficient at clearing the infection. 28,29 It is logical to assume that, if acupuncture treatment can restore the balance of the Th1/Th2 response in Th2-related diseases as noted, it may be possible to do so in the case of chronic HPV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have reported suppression of local immune response mediated by dysfunctional natural killer (NK) cells, dysfunctional Langerhans cells, and resultant T-helper cells skewing toward Th2 phenotype at the local disease site. [10][11][12] The Langerhans cells in HPV-infected lesions appeared in clumps with altered distribution and morphology 13,14 and no surface expression of maturation marker CD83. 15 It has been found that proportion of T-regulatory cell correlated with the size of the warts.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that cell mediated immune responses of the host, both systemic and local, are important determinants of the course of infection (Amador-Molina et al, 2013). This immune response is mediated through the release of various cytokines, which can influence the synthesis and actions of other cytokines; the setting known as an immunoregulating cytokine network.…”
Section: Introductionmentioning
confidence: 99%